EVALUASI PENERAPAN SUPPLY CHAIN PADA CV. X - AGUSTIN, HARIANTI (Jurnal Akuntansi AKUNESA, 2015)
Supply chain is an integrated chain from the supplier to distribute the goods into the end customer. The supply chain’s implementation is an important part to improving the business competition. CV. X is one of furniture company that sells many furnitures item like chairs, tables, spring bed, and so on. As a furniture company CV. X requires a qualified supplier to match the customer's order. So that, CV. X must implement supply chain with the right strategy. That’s strategy is having one supplier or chose many supplier. To expand the business network, CV. X need to keep their partnerships. Supply chain of CV. X start from the shop in Karah Lapangan No. 2 Surabaya and factories in Margomulyo and then routed to the CV. X. The next chain is distribute merchandise to consumers, including CV. Y which will distribute the goods to one university on Surabaya.Keywords: Supply chain, Distribution, Implementation.